A national service for delivering CD19 CAR‐Tin large B‐cell lymphoma – The UK real‐world experience. (29th April 2022) - Kuhnl, Andrea; Roddie, Claire; Kirkwood, Amy A.; Tholouli, Eleni; Menne, Tobias; Patel, Amit; Besley, Caroline; Chaganti, Sridhar; Sanderson, Robin; O'Reilly, Maeve; Norman, Jane; Osborne, Wendy; et al.
Summary: CD19 CAR‐T have emerged as a new standard treatment for relapsed/refractory (r/r) large B‐cell lymphoma (LBCL). CAR‐T real‐world (RW) outcomes published to date suggest significant variability across countries. We provide results of a large national cohort of patients intended to be treated with CAR‐T in the UK. Consecutive patients with r/r LBCL approved for CAR‐T by the National CAR‐T Clinical Panel between December 2018 and November 2020 across all UK CAR‐T centres were included. 404/432 patients were approved [292 axicabtagene ciloleucel (axi‐cel), 112 tisagenlecleucel (tisa‐cel)], 300 (74%) received the cells. 110/300 (38.3%) patients achieved complete remission (CR) at 6 months (m). The overall response rate was 77% (52% CR) for axi‐cel, 57% (44% CR) for tisa‐cel. The 12‐month progression‐free survival was 41.8% (axi‐cel) and 27.4% (tisa‐cel). Median overall survival for the intention‐to‐treat population was 10.5 m, 16.2 m for infused patients. The incidence of grade ≥3 cytokine release syndrome and neurotoxicity were 7.6%/19.6% for axi‐cel and 7.9%/3.9% for tisa‐cel. This prospective RW population of CAR‐T eligible patients offers important insights into the clinical benefit of CD19 CAR‐T in LBCL in daily practice. Our results confirm long‐term efficacy in patients receiving treatment similar to the pivotal trials, but highlight the significance of early CAR‐T failure.